2020
DOI: 10.5812/ijpbs.102317
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Alexithymia Across Positive and Negative Emotions: The Psychometric Properties of the Iranian Version of the Perth Alexithymia Questionnaire

Abstract: Background: Construct of Alexithymia is important for understanding psychopathology that its assessment is of high interest as persons with difficulty in processing their emotions (either positive and negative) are more vulnerable to psychopathology problems. Objectives: The current study aimed to determine the psychometric properties of the Perth Alexithymia questionnaire (PAQ), and to describe appropriate measures for the field of clinical psychology and psychiatry. Methods: The Persian version of the PAQ wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…All subscales, especially the total alexithymia, indicated good test-retest reliability, which means that the scale results are consistent at different time points. The test-retest reliability results in the present study are comparable with those reported by Mousavi Asl et al (2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All subscales, especially the total alexithymia, indicated good test-retest reliability, which means that the scale results are consistent at different time points. The test-retest reliability results in the present study are comparable with those reported by Mousavi Asl et al (2020).…”
Section: Discussionsupporting
confidence: 91%
“…As we know, EOT component of the Farsi version of TAS-20 has lower internal consistency (Besharat, 2008). Besides, other studies aimed at validating PAQ in Iran failed to recruit a big enough sample or to report confirmatory analysis (Heydari et al, 2020;Mousavi Asl et al, 2020). Accordingly, the current study aimed to examine the validity and reliability of PAQ in Iran with specific reference to its internal consistency, testretest reliability, concurrent and discriminant validity, and factor structure.…”
Section: Introductionmentioning
confidence: 92%
“…As such, future work will be needed to test the generalisability of our findings. That said, our study lends further support to the cross-cultural validity of the PAQ, largely mirroring the results of past studies conducted in other languages ( 14 16 , 18 ). This reflects the strengths of the Polish version of the PAQ and presents a good support for conducting the studies on clinical and adolescent samples.…”
Section: Discussionsupporting
confidence: 87%
“…Originally developed in English, several language translations of the PAQ have now been published, including Turkish ( 15 ), Iranian ( 16 , 17 ), and Spanish ( 18 ) versions. Factor analyses across language versions have consistently supported a 5-factor structure, conforming to the intended five factors ( 13 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…While alexithymia is the inability to empathize and relate to others, “emotion without speech” or “lack of words for emotions” indicates difficulty in expressing verbal emotions (Asl et al, 2020 ), and both are serious issues in the nursing profession. With the shift of medical education from purely theoretical teachings to human communication (Kurtz et al, 2017 ), alexithymia has become one of the variables used in assessing the competence and ability of nursing students (Expósito et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%